Nationalism : theory, ideology, history - Smith, Anthony D. (Cambridge, UK ; Malden, MA : Polity, 2010)
For the last two centuries, nationalism has been a central feature of society and politics. Few ideologies can match its power and resonance, and no other political movement and symbolic language has such worldwide appeal and resilience. But nationalism is also a form of public culture and political religion, which draws on much older cultural and symbolic forms. Seeking to do justice to these different facets of nationalism, the second edition of this popular and respected overview has been revised and updated with contemporary developments and the latest scholarly work. It aims to provide a concise and accessible introduction to the core concepts and varieties of nationalist ideology; a clear analysis of the major competing paradigms and theories of nations and nationalism; a critical account of the often opposed histories and periodization of the nation and nationalism; and an assessment of the prospects of nationalism and its continued global power and persistence. Broad and comparative in scope, the book is strongly interdisciplinary, drawing on ideas and insights from history, political science, sociology and anthropology. The focus is theoretical, but it also includes a fresh examination of some of the main historical and contemporary empirical contributions to the literature on the subject. It will continue to be an invaluable resource for students of nationalism across the social sciences. -- Back cover.
Concepts -- Ideologies -- Paradigms -- Theories -- Histories -- Prospects.
Includes bibliographical references (pages 177-196) and index.
Keywords: Nationalism; Politics and Government; Nationalism; Politics and Government; Deutschland; England; Educational tools (form)